Efek Asap Cair Gelam (Melaleuca sp) sebagai Pengawet terhadap Berat Kayu dan Berat Jenis Terantang (Campnosperma auriculatum (BI.) Hook.f) - Alpian, Alpian; Samosir, July Sarana Dame; Yanciluk; Tanduh, Yusintha; Silvianingsih, Yosefin Ari; Supriyati, Wahyu; Luhan, Gimson (Jurnal Penelitian Hasil Hutan, 2025)
Terantang is commonly found growing in the peat swamp forests of Central Kalimantan. It holds significant economic value in the wood processing industry; however, it has low durability, requiring preservation treatments to enhance its wood quality. This study aims to analyze the impact of Gelam wood liquid smoke concentration and the radial direction of Terantang wood on its physical properties, particularly wood weight and specific gravity, after being stored outdoors under shaded conditions for 5 weeks. A factorial Completely Randomized Design (CRD) was employed, incorporating two factors: liquid smoke concentration (0%, 10%, 20%, and 30%) and radial direction of the wood (near the bark, middle, and near the pith). The data were analyzed using ANOVA, followed by Tukey’s HSD test to determine significant differences between treatments. The results indicated that increasing the concentration of liquid smoke significantly enhanced both the wood weight and specific gravity. The 30% liquid smoke concentration produced the highest increase in specific gravity (0.5240 g/cm³). The radial direction of the wood also had a significant effect, with the near-pith section showing higher specific gravity. The interaction between liquid smoke concentration and radial direction significantly influenced the wood weight. These findings suggest that Gelam wood liquid smoke is an effective natural preservative that can significantly maintain the physical quality of Terantang wood stored outdoors under shaded conditions for 5 weeks, specifically in terms of wood weight and specific gravity. This method shows potential for use in sustainable wood processing industries.